2010
DOI: 10.1186/1824-7288-36-44
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing knowledge about childhood autism among final year undergraduate Medical, Nursing and Psychology students of University of Nigeria, Enugu State, Nigeria

Abstract: BackgroundKnowledge and awareness about childhood autism is low among health care workers and the general populace in Nigeria. Poor knowledge about childhood autism among final year medical, nursing and psychology students who would form tomorrow's child health care professionals can compromise early recognition and interventions that are known to improve prognosis in childhood autism. Educational factors that could be influencing knowledge about childhood autism among these future health care professionals ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 13 publications
4
54
3
Order By: Relevance
“…Multivariate analysis also showed that there were significant associations between scores of knowledge of childhood ASD and specialty. Monday et al reported that medical students had a statistically higher score of ASD knowledge than nursing students (15). The difference in knowledge found among the healthcare workers between doctors and nurses in our study is likely to be due to the discrepancies of schools curricula, as well as occupational history.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Multivariate analysis also showed that there were significant associations between scores of knowledge of childhood ASD and specialty. Monday et al reported that medical students had a statistically higher score of ASD knowledge than nursing students (15). The difference in knowledge found among the healthcare workers between doctors and nurses in our study is likely to be due to the discrepancies of schools curricula, as well as occupational history.…”
Section: Discussioncontrasting
confidence: 47%
“…In this study, Chongqing, the Chinese fourth municipality, with a large area and large population of children (14) was selected to explore the knowledge and attitudes of childhood ASD among child healthcare workers in grassroots health service institutes. The study may further contribute to a growing body of literature concerning early diagnosis and intervention efforts (15). This research may also help to delineate the impact of policy initiatives in China, which has begun to help the needs of ASD children by expanding financial assistance (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of many studies in Nigeria show a low level of knowledge and awareness about autism spectrum disorders in Africa, thereby compromising early recognition of the disorder and intervention to alleviate symptom severity (ANPPCAN, 2007;Bakare et al, 2008;Bakare et al, 2009b;Igwe et al, 2010;Igwe et al, 2011). African Network for the Prevention and Protection against Child Abuse and Neglect (ANPPCAN), Nigeria chapter, in a World Bank sponsored program carried out a survey to determine the level of knowledge and awareness of health care workers and the general public in Enugu, south-eastern Nigeria about autism spectrum disorders (ANPPCAN, 2007).…”
Section: Knowledge and Awareness About Autism Spectrum Disorders In Amentioning
confidence: 99%
“…It was further established that the ability of healthcare workers working in psychiatric facilities to recognize symptoms of autism spectrum disorder was better than their counterparts working in pediatric units/departments (Bakare et al, 2009b). Igwe et al (2010) examined level of knowledge about autism spectrum disorders among potential health care workers presently undergoing their training; they compared final year medical, nursing and psychology students of University of Nigeria in Enugu State, south-eastern Nigeria. Medical students were more likely to recognize symptoms of autism spectrum disorders, followed by nursing and then psychology students.…”
Section: Knowledge and Awareness About Autism Spectrum Disorders In Amentioning
confidence: 99%